Festivals and Ceremonies of the Alaskan Eskimos: Historical and Ethnographic Sources, 1814-1940 - Salius Gumà, Jesús (Revista Española de Antropología Americana, 2015)
The main objective of this article is to shed light on the festive and ceremonial events of some of the Eskimo cultures of Alaska through a review of the ethnohistorical documents at our disposal. The study centers on the ancient societies of the Alutiiq, Yup’ik and a part of the Inupiat, communities that share a series of common features, and sees their festive and ceremonial activities as components of the strategies implemented to maintain control over social reproduction. This review of the historical and ethnographic sources identifies the authors and the studies that provide the most pertinent data on the subject. El objeto de este artículo es arrojar luz sobre las fiestas y ceremonias de algunas culturas esquimales de Alaska a través de la revisión de documentos etnohistóricos a nuestra disposición. La investigación se centra sobre las antiguas sociedades de los alutiiq, yup’ik y parte de los inupiat, comunidades que tienen una serie de rasgos comunes y contemplan sus actividades festivas y ceremoniales como parte de estrategias para mantener el control sobre la reproducción social. Esta revisión de fuentes históricas y etnográficas identifica a los autores y a los estudios que proporcionan los datos más significativos sobre el tema.